Effect of Situational Factors on the Rate of Perceived Exertion of Liga Femenina 2 Players - García, D.; Escobar R.; Piñar M. I. (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The aim of the study is to understand the impact of certain situational variables (game location, season phase, game outcome, score-line and quality of opposition) on the rate of perceived exertion (RPE) of women players of Liga Femenina 2 in competition. 24 matches played by 12 players of a team from group B of Liga Femenina 2 of the Spanish Basketball Federation during the 2019/2020 season were analysed. The RPE of the players was collected between 20 and 30 minutes after the end of the game. A multiple regression analysis was performed, considering the five situational variables as predictors of RPE. The results show that 44.61% of the RPE values are explained by these situational variables in a statistically significant way. Of the 5 situational variables analysed, the game location and the quality of opposition are dependent on the RPE. Playing away and against a weaker opponent is directly related to a higher RPE of the players in competition.